Проблеми та перспективи забезпечення енергетичної безпеки ЄС під час російської агресії проти України - Садигов, С. А. О. (НДІ ПЗІР НАПрН України, 2022)
Наукове дослідження висвітлює актуальні проблеми залежності Європейського Союзу (далі – ЄС) від поставок енергетичних ресурсів з Росії на тлі військової агресії в бік України та обґрунтовується значимість подолання такої залежності. Вторгнення в Україну істотно похитнуло стан енергетичної безпеки держав-членів ЄС та всього європейському континенту загалом. Це, в свою чергу, активізувало процес розробки нової та вдосконалення існуючої правової бази ЄС в енергетичній сфері у максимально звужені строки. Автор статті аналізує сукупність законодавчих ініціатив ЄС, що мають на меті допомогти державам-членам пройти опалювальний сезон без масштабних потрясінь. З проаналізованих автором пропозицій Європейської Комісії вбачається, що істотний внесок у подолання європейської енергетичної залежності від Росії можуть внести положення трансформаційного плану REPowerEU, що передбачає використання для потреб ЄС екологічно чистої енергетики. Автор доходить до висновку, що економічно ефективне, швидке та широкомасштабне розгортання сталої відновлювальної енергії відповідно до положень Європейської зеленої угоди та повідомлення REPowerEU не може бути досягнуто державами-членами самостійно. Визначено, що нівелювання негативних наслідків неможливе без ефективної координації та об’єднанні дій всіх держав-членів ЄС. Останні десятиліття енергетична політика є центральним пунктом зовнішньої політики ЄС та наразі виступає джерелом багатьох суперечок, які перешкоджають спробам ЄС налагодити стратегічні відносини зі своїми сусідами та постачальники енергії. Тому дослідження проблем залежності від третіх країн та пошук шляхів їх вирішення відповідає найважливішим потребам сучасності та має суттєве значення для подальшого розвитку енергетичного сектору ЄС. Підсумовано, що така сукупність заходів неодмінно буде супроводжуватися наслідками економічного характеру в бюджетній сфері, в інвестиційній політиці, структурі галузевого виробництва, в сфері амортизаційних видатків, ціновій політиці та оподаткуванні тощо. Problem setting. The article highlights the topical problems of the EU’s dependence on the supply of energy resources from Russia against the background of military aggression towards Ukraine and substantiates the importance of overcoming such dependence. Analysis of resent researches and publications. A considerable number of scientific papers published in recent years shows that the issues of energy security and legal support of cooperation between the EU Member States in the energy sector have often been studied by Ukrainian and foreign scientists both lawyers and economists. Currently, in legal and economic doctrines, the sphere of energy relations and, in particular, energy security is most often associated with the names of S. D. Bilotskyi, T. A. Grabovych, R. R. Dubas, M. V. Muzychenko, M. Roggenkamp, K. Talus, P. D. Cameron and others. The war in Ukraine has significantly intensified attempts to maintain a proper state of energy security in Europe and, accordingly, scientific developments in this sphere. Аrticle’s main body. The invasion in Ukraine significantly sway the state of energy security of the EU member states and the entire European continent in general. This, in turn, activated the process of developing a new and improving the existing EU legal framework in the energy sector in the shortest possible time. The author analyzes a set of EU legislative initiatives aimed at helping member states to get through the heating season without large-scale upheavals. From the proposals of the European Commission analyzed by the author, it can be seen that the provisions of the REPowerEU transformation plan, which provides for the use of ecologically clean energy for the needs of the EU, can make a significant contribution to overcoming European energy dependence on Russia. The author comes to the conclusion, that economically effective, rapid and wide-range development of sustainable renewable energy in accordance with the theses of the European Green Deal and the REPowerEU communication can’t be attained by states-members independently. Certainly, that leveling of negative consequences is impossible without effective co-ordination and association of actions of all EU member states. Last decades power politics is the central point of foreign policy of EU and now comes forward as a source of many spores that prevent to the attempts of EU to put right strategic relationships with the neighbours and suppliers of energy. Therefore, research of problems of dependence on the third countries and search of ways of their decision answer the major necessities of contemporaneity and has a substantial value for further development of the EU energy sector. It is concluded that such a set of measures will certainly be accompanied by consequences of an economic nature in the budgetary sphere, in investment policy, the structure of industry production, in the sphere of amortization expenses, price policy and taxation, etc. Conclusions and prospects for the development. The challenges and uncertainties facing the European energy system are the biggest in almost fifty years, since the great energy crises of the 1970s, and therefore the set of measures to overcome the consequences of the war in Ukraine for the EU energy sector is unprecedented. Cost-effective, rapid and large-scale deployment of sustainable renewable energy in line with the provisions of the European Green Deal and the REPowerEU Communication cannot be achieved by Member States on their own. Taking into account the different energy policies between Member States, action at EU level, backed by a robust governance structure, is more likely to achieve the EU’s climate goals and will require a greater deployment of renewables than national or local measures alone. Further measures could also include regulation of gas supply in the form of improved coordination of gas procurement and promotion of joint purchases by European gas market operators on the international market. Furthermore, it would be advisable to consider over time legislative measures to require diversification of gas supplies from individual Member States that have had such experience in the past. Particular attention should also be paid to improving the energy partnership with Ukraine. This would address the issues related to the importance of Ukraine as a transit country as well as those related to the reforms of the Ukrainian energy market, such as the modernisation of the gas network, the establishment of an appropriate regulatory framework for the electricity market and the improvement of energy efficiency in Ukraine as a means of reducing its dependence on imported energy. In the near future, the intention is to strengthen cooperation in the energy sector with the Energy Community, which will ensure closer integration of the EU and Energy Community energy markets, effective implementation of the EU environmental policy and stimulate investments in the energy sector.
Keywords: Європейський Союз; енергетична безпека; війна в Україні; відновлювальні джерела енергії; енергетичні ресурси; Європейська зелена угода; European Union; energy security; war in Ukraine; renewable energy sources; energy resources; European Green Deal